Mountain medicine development in Nepal: Karnali Academy of Health Sciences as strategic institution - Upadhyay-Dhungel, Kshitiz (Journal of Karnali Academy of Health Sciences, 2025)
Nepal, home to most of the world’s highest mountain peaks, presents both challenges and opportunities for healthcare delivery, particularly in mountain medicine. It requires tailored approaches to medical care, emergency response, and health research as it is characterized by rugged terrain, limited infrastructure, and diverse cultural settings. This editorial explores the concept of mountain medicine, tracing its historical evolution, outlining its current scope, and discussing its future potential in the Nepalese context. It further proposes the Karnali Academy of Health Sciences (KAHS) as a strategic institution to advance mountain medicine in Nepal, emphasizing interdisciplinary collaboration, capacity building, and sustainable practices. The article advocates integrating mountain medicine into Nepal’s health system to improve outcomes for local communities, mountaineers, and visitors, and highlights KAHS as a key institution to lead these efforts.